Dysnatremia and mortality: do sweat the small stuff... - Klinck, John R (BioMed Central, 2013)
Marked dysnatremia is associated with increased mortality in patients admitted to intensive care. However, new evidence suggests that even mild deviations from normal and simple variability of sodium values may also be significant. Should these findings prompt clinicians to re-evaluate the approach to fluid management in this setting? Sodium disorders, on one hand, are known to result from overzealous administration or restriction of free water or sodium ions. However, they are also associated with a range of co-morbidities and drug treatments that alter water loss and sodium handling in the nephron independently of prescribed fluid regimens. Moreover, powerful neuroendocrine and inflammatory responses to surgery, trauma and other acute illness may induce or intensify such changes, altering the response to administered fluids. These observations suggest that both patient and treatment variables contribute, but the extent to which sodium disturbances are preventable and whether prevention improves outcome are unknown. Dysnatremia certainly reflects underlying systemic disorders, but how important is fluid management as a cause, and does it contribute independently to poorer outcomes through osmotic or other mechanisms? Although total fluid volume and doses of potassium and glucose are regularly adjusted in critically ill patients, sodium is usually delivered at standard concentrations as long as serum values lie within an acceptable range. It may be prudent to pay closer attention to these values, especially when abnormal, when fluctuating or when an adverse trend is present. More frequent measurements of sodium in blood, urine and drainage fluids, and appropriate adjustment of the sodium content of prescribed fluids, may be indicated. Until more light can be shed on the pathophysiology of dysnatremia in the critically ill, we should assume that better control of plasma sodium levels may yield better outcomes.